Discovery of non-spherical heterogeneous radiocesium-bearing particles not derived from Unit 1 of the Fukushima Dai-ichi Nuclear Power Plant, in residences five years after the accident. (October 2017) - Higaki, Shogo; Kurihara, Yuichi; Yoshida, Hiroko; Takahashi, Yoshio; Shinohara, Naohide
Abstract: Non-spherical heterogeneous radiocesium-bearing particles were found on masks worn during cleaning work in residences near the Fukushima Dai-ichi Nuclear Power Plant (FDNPP), from which residents had evacuated. Three slightly larger (6.6–12 μm) non-spherical radiocesium-bearing particles were found in a residence in Futaba Town, a straight distance of 2.11 km west-northwest from the FDNPP. These were collected on October 25, 2016, 5 years and 7 months after the Fukushima Dai-ichi nuclear disaster and were presumed to originate from the Plant's Unit 2 based on the measured radioactivity ratio of 134 Cs/ 137 Cs. The main elemental composition was similar to particles already reported in other studies. However, this is the first time that such particles had a clearly heterogeneous distribution. Highlights: Unusual radioactive particles were found near the Fukushima Daiichi plant. These particles remained inside a house in 2016, 5 years after the accident. These particles' composition and structure are different from any previously known.